THE ECONOMIC AND PSYCHOLOGICAL ADVANTAGES OF LOCAL RECREATIONAL TOURISM IN BUKHARA - Madina Sayfullayeva (Journal Park Publishing, 2025)
Bukhara, a UNESCO World Heritage site, is renowned for its historical and cultural significance. However, the city’s potential for recreational tourism at the local level remains underexplored. This article investigates the economic and psychological benefits of developing local recreational tourism in Bukhara, emphasizing its role in diversifying the city’s tourism offerings beyond heritage attractions. Using qualitative and quantitative data, the study highlights how local recreational tourism can stimulate economic growth, reduce travel-related stress, and foster community well-being. The findings underline that sustainable investment in recreational infrastructure and activities can enhance Bukhara’s appeal for both residents and visitors.
Keywords: Recreational tourism, local tourists, economic impact, psychological impact, sustainability, domestic tourism, international tourism.